Quantitative Assessment of Polycyclic Aromatic Hydrocarbons from Corkwaste Combustion Emissions (Journal of Agricultural Engineering Research, 2000)
Cork is a natural raw material obtained from the cork oak (Quercus suber). The corkwaste is a potential source of polycyclic aromatic hydrocarbons (PAHs) due to its high content of volatile compounds. A sampling method was developed for the measurement of polycyclic aromatic hydrocarbons emissions in a pilot bubbling #uidized bed combustion. This method has been designed to assess simultaneously the PAH contained in the gas phase and in the particulate matter. The samples were analysed on a gas chromatography coupled to a mass spectrometer to identify and quantify PAH compounds. The mass-selective detector was run in the selected ion monitoring mode. This study shows that lower molecular weight PAH were present predominantly in the gas phase, whereas high weight PAHs were retained in the particulate phase. As there is an existing relationship between the emission of CO and polycyclic aromatic hydrocarbons, the control and assessment of both compounds have been performed.

Quantitative Assessment of Polycyclic Aromatic Hydrocarbons from Corkwaste Combustion Emissions - Cabañas, Aracel; Sáez, Felicia; González, Alberto; Escalada, Ricardo (Journal of Agricultural Engineering Research, 2000)
Cork is a natural raw material obtained from the cork oak (Quercus suber). The corkwaste is a potential source of polycyclic aromatic hydrocarbons (PAHs) due to its high content of volatile compounds. A sampling method was developed for the measurement of polycyclic aromatic hydrocarbons emissions in a pilot bubbling #uidized bed combustion. This method has been designed to assess simultaneously the PAH contained in the gas phase and in the particulate matter. The samples were analysed on a gas chromatography coupled to a mass spectrometer to identify and quantify PAH compounds. The mass-selective detector was run in the selected ion monitoring mode. This study shows that lower molecular weight PAH were present predominantly in the gas phase, whereas high weight PAHs were retained in the particulate phase. As there is an existing relationship between the emission of CO and polycyclic aromatic hydrocarbons, the control and assessment of both compounds have been performed.
Keywords: Cork waste; Fluidized bed combustion (PG); GC-MS; Polycyclic aromatic hydrocarbons (PAHs)